Arabian Journal of Geosciences - Arabian Journal of Geosciences (Springer Nature, 2026)
The official journal of the Saudi Society for Geosciences, the Arabian Journal of Geosciences examines the entire range of earth science topics focused on, but not limited, to those that have regional significance to the Middle East and the Euro-Mediterranean Zone.
FI 0.46
N/A
Keywords: Earth; Space & Environmental Sciences; Earth Sciences; Ciencias de la Tierra; Acuerdos transformativos; Transformative agreements; Ciencias Atmosféricas; Meteorología; Climatología; Oceanografía